Types of Code switching Found in Podcast Friends of Merry Riana by Naura Ayu and Merry Riana - Dewi, Bintang Duwari (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Most celebrity in Indonesia use English mix with Indonesian language in their utterance. Therefore, code switching frequently becomes evident in those instances. The primary aims of this study involve recognizing the various forms of code switching that appear in the video podcast dialogues between Naura Ayu and Merry Riana on YouTube.. This study used descriptive qualitative method to analysis data. The theory proposed by Appel and Muysken (1987) is employed to classify the various forms of code switching. For the result of this research demonstrate that within the statements made by Naura Ayu and Merry Riana, the prevailing form of code switching is intra-sentential switching. This happens because Naura Ayu and Merry Riana often insert English into Indonesian speech which is still in one utterance.